Kajian Mengenai Niat Keusahawanan Mengikut Teori Tingkah Laku Terancang - Ramli, Nurul Jasmin; Abu Seman, Noor Aslinda (Research in Management of Technology and Business, 2020)
In the global fast changing socio-economic environment, entrepreneurship is an important position in the economy. Entrepreneurship has become a critical factor of the economic growth and plays an influential role in the standard of living in the country. Therefore, the purpose of this study is to identify the relationship between attitude towards behaviour, subjective norm and perceived behavioural control towards entrepreneurial intention among final year student in Kolej Kemahiran Tinggi Mara (KKTM) Batu Pahat, Johor. In addition, this study uses quantitative methods by distributing questionnaires to respondents among students. Baed on the Krejcie & Morgan sample size table, 155 respondents should be involved in this study. However, only 111 successful questionnaires were returned. The Statistical Packages for Social Science (SPSS) software is used to analyze data. The analysis consists of descriptive analysis and correlational analysis. The result shows that there is significant relationship between attitude towards behaviour, subjective norm and perceived behavioural control towards entrepreneurial intention among final year student in Kolej Kemahiran Tinggi Mara (KKTM). This study is important to expand the understanding of the researchers toward the entrepreneurial intention among students.